2018
DOI: 10.2463/mrms.mp.2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Seromucinous Borderline Tumor from Serous Borderline Tumor on MR Imaging

Abstract: Purpose:Seromucinous borderline tumor (SMBT) is a newly categorized ovarian tumor in the 2014 revised World Health Organization (WHO) classification. SMBT is similar to serous borderline tumor (SBT) on MRI reflecting their pathological findings. This study was conducted to demonstrate the usefulness of MRI findings and quantitative values for differentiating SMBT from SBT.Methods:This retrospective study examined 23 lesions (20 patients) from SMBT and 26 lesions (22 patients) from SBT. The following quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This finding is in good agreement with that of Kurata et al, reporting that SMBT showed a high intracystic fluid signal intensity on T1WI and a low signal intensity on T2WI. [2] The intracystic fluid signal intensity depends upon the electron paramagnetic effects of the different derivates of hemoglobin (oxyhemoglobin, methemoglobin, heme iron, and free iron) and the magnetic field strength. [12] Recent metallobiology study demonstrated that methemoglobin (ferric Fe 3+ ) was significantly more abundant in cyst fluids of benign OE than EAOC patients, while oxyhemoglobin (ferrous Fe 2+ ) was significantly more abundant in the cyst fluids of EAOC than benign OE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in good agreement with that of Kurata et al, reporting that SMBT showed a high intracystic fluid signal intensity on T1WI and a low signal intensity on T2WI. [2] The intracystic fluid signal intensity depends upon the electron paramagnetic effects of the different derivates of hemoglobin (oxyhemoglobin, methemoglobin, heme iron, and free iron) and the magnetic field strength. [12] Recent metallobiology study demonstrated that methemoglobin (ferric Fe 3+ ) was significantly more abundant in cyst fluids of benign OE than EAOC patients, while oxyhemoglobin (ferrous Fe 2+ ) was significantly more abundant in the cyst fluids of EAOC than benign OE.…”
Section: Discussionmentioning
confidence: 99%
“…Seromucinous borderline tumor (SMBT) is frequently associated with endometriosis that is a common gynecological disorder affecting women in the reproductive age group. [1,2] Endometriosis is a benign condition, but approximately 1% of the cases undergo malignant transformation (endometriosis-associated ovarian cancer [EAOC]) later in life. [3] EAOC includes clear cell carcinoma, endometrioid carcinoma, low-grade serous carcinoma, and SMBT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study which looked at the MRI findings of seromucinous tumors found evidence of endometriosis in more than half the cases and concluded that it was difficult to differentiate tumors diagnosed as seromucinous carcinomas from other endometriosis related carcinomas by imaging studies [ 14 ]. However, some other recent imaging studies have found certain imaging features on MRI which can help in distinguishing seromucinous tumors from other malignant ovarian tumors including endometriosis related tumors [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRI findings reflect these pathological characteristics, and it appears as an endometriotic cyst with papillary mural nodules (Fig. 12 ) [ 39 ]. The mural nodules show as dendritic hypointensity with surrounding markedly hyperintense areas on T2WI (Fig.…”
Section: Cystic Mass With Mural Nodule or Solid Component Related To ...mentioning
confidence: 99%